(untitled) (Revista Cocar, 2012)
Este relato de experiência apresenta resultados do uso da calculadora no ensino das operações com números relativos em uma turma da 6ª serie do ensino fundamental de uma escola pública de Santa Luzia do Pará. Os resultados indicam que o uso de calculadoras simples com tal fim é uma alternativa viável e de efeitos significativos. Palavras-chave: Ensino de números. Relativos. Uso didático da máquina de calcular. Aritmética. Calculator, redescovering activities and games in the relative numbers teaching. This work presents some outcomes of an experience concerning the use of a calculator in the relative numbers operation teaching in a class of "the 6th grade of the Fundamental Teaching, from a public school in the city of "Santa Luzia of Pará. The results suggest that the use of simple calculators is a good alternative to this kind of activity and its outcomes are significant. Keywords: Relative numbers teaching. Calculatorâ€™s didactic usage. Arithmetic